Activity of Xanthine Oxidase during Transition Period and Its Association with the Occurrence of Postpartum Infections in Murrah Buffalo (Bubalus bubalis) - Bhabesh Mili; Sujata Pandita; B. S. Bharath Kumar; Anil Kumar Singh; Madhu Mohini; Manju Ashutosh (Newest Updates in Agriculture and Veterinary Science Vol. 1, 2022)
The purpose of this study was to evaluate the relationship between Xanthine Oxidase (XO) levels during the transition period in Murrah buffalo (Bubalus bubalis) and different postpartum infections. Practices of feeding, breeding, health and housing management have a great influence on buffalo performance and ultimately influence dairy farmers’ economy. Among all, reproductive performance is of major concern which possibly determines all other components of income generation in any organized dairy farm. For this, six healthy buffaloes were selected from the ICAR-National Dairy Research Institute (ICAR-NDRI) herd and managed under standard managemental practices as followed at the institute. Blood samples were drawn weekly from each buffalo from day -21 to +21 relative to parturition by jugular vein puncture. Additional blood samples were collected from buffaloes suffering from metritis (n=5), endometritis (n=6) and mastitis (n=8) on alternate days. XO activity followed a defined pattern with values gradually declining from day -21 up to the day of calving followed by an increase to day +21, but the difference was statistically not significant between pre- and post-partum stages. The activity significantly declined on the day of calving when compared to the pre-partum mean value (p<0.05). The activity was significantly enhanced in buffaloes with bacterial infections, endometritis, and mastitis compared to healthy controls (p<0.05). However, the levels were not significantly altered among buffalo with metritis. The results indicate that increased XO activity during the postpartum period was associated with some bacterial infections in buffaloes, which could be due to increased phagocytic activity as a part of the innate defense system. It could also be employed as an inflammatory marker in buffaloes with postpartum bacterial infections. More research is needed to validate it as a risk factor for uterine infections.